Measuring distance between nearly intersected objects in narrow phase collision detection - Sulaiman, Hamzah Asyrani; Bade, Abdullah; Othman, Mohd Azlishah; Ramlee, Ridza Azri; Misran, Mohamad Harris; Zainudin, Muhammad Noorazlan Shah; Abdullah, Mohd Harun (2013)
Calculating the distance between two or more object primitives (or triangles) in virtual environment application before collision occurs is important elements in narrow phase collision detection system. Given pairs of nearly colliding objects, their triangles must be checked one by one until the most shortest distance is founded and thus the computation cost for checking collision reduced by checking the nearest triangles that possible to collide. Hence, in this research, we used Heron’s formula for calculating the distance between objects that nearly collide and compared it using vector-based calculation. We have found that the formula increased the speed of distance computation slightly faster compared to the vector-based calculation for single triangle checking with minimum memory requirements. In this paper, we explained the procedures of using Heron’s Formula and vector-based techniques for computing distance and the experimental results between those two techniques. It is believed that it could help to speed up the process of determine the precise contact between colliding objects while maintaining the accuracy of the collision checking